The ScFRK2 mitogen-activated protein kinase kinase kinase (MAP3K) is involved in early embryo sac development in Solanum chacoense. (3rd August 2019) - Mazin, Benjamin D.; Joly, Valentin; Matton, Daniel P.
ABSTRACT: Fertilization-related kinase (FRK) is a group of the mitogen-activated protein kinase kinase kinase (MAP3K or MEKK) that has proliferated in Solanaceae species. Studies on the wild potato Solanum chacoense have shown that three ScFRKs are directly involved in female gametophyte development. Decreasing the expression of ScFRK1 and ScFRK3 by RNA interference lead to embryonic sac development arrest at the functional megaspore (FM) stage. As for ScFRK2, the first FRK studied, antisense and co-suppression lines showed no abnormality, while overexpression lines lead to a drastic decrease in seed numbers, presumably caused by a conversion of the ovule into a carpel-like structure. Here we show that in ScFRK2 overexpression lines, carpel-like structures from the ovule cannot explain the drastic decrease in seeds considering the low percentage of these carpel-like structures but occurs in early ovule development as observed in Scfrk1 and Scfrk3 knockdown mutants were most ovules are arrested at the FM stage. The highly similar phenotype from knockdown mutants ( Scfrk1 and Scfrk3 ) and ScFRK2 overexpression lines suggests that these MAP kinases could operate antagonistically through a balance between ScFRK1 and 3 on one side and ScFRK2 on the other. This study strongly suggests the importance of the FRK family expression levels during early stages of ovule development in Solanum chacoense embryo sac.